Optimasi Waktu Fermentasi Biji Kakao (Theobroma cocoa L.) Menggunakan Ragi Tape Terhadap Aktivitas Antioksidan Dengan Metode DPPH - Pratiwi, Dian; Ika Pramitha, Dewa Ayu; Kusuma Wardani, I Gusti Agung Ayu (Usadha, 2025)
Cocoa beans (Theoborma cacao L.) are one part of the cocoa plant that is believed to contain high levels of polyphenol compounds that act as antioxidants. Cocoa beans are said to contain high polyphenol and flaovonoid compounds, which play an important role in the formation of antioxidants. Fermented cocoa beans have better quality in terms of taste, aroma, and color, but the fermentation process can cause a decrease in the content of polyphenol compounds in cocoa beans, causing a decrease in antioxidant activity. In the fermentation process, adding fermenters such as yeast tape can shorten the fermentation time. This study aims to determine the optimization of fermentation time to produce higher antioxidant activity of cocoa beans (Theobroma cacao L.) using the DPPH method. The results of the cocoa bean antioxidant test showed the IC50 value in the unfermented cocoa bean sample was 15.360 ppm, in the 1st day fermentation sample was 23.757 ppm, in the 2nd day fermentation sample was 3.574 ppm, in the 3rd day fermentation sample was 7.985 ppm, in the 4th day fermentation sample was 27.70 ppm, in the 5th day fermentation sample was 33.111 ppm, in the 6th day fermentation sample was 2.456 ppm, and in ascorbic acid as a positive control was 2.463 ppm. The data showed that the most optimum antioxidant value was found in the sample fermented for 6th days.